2000
DOI: 10.1080/002411600750053853
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and extinction patterns of Permian coral faunas of China

Abstract: Coral diversity and extinction patterns in the Permian of China are revealed through statistical analyses of 56 coral families, 263 genera and 2100 species from five consecutive time intervals. The highest coral diversity is in the Chuanshanian, with 753 species, 167 genera and 39 families. In contrast, the lowest diversity is in the Changhsingian, with only 68 species, 20 genera and 10 families. Two decreases in diversity can be recognized during the Permian. The first occurred at the end of the Maokouan (end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(24 citation statements)
references
References 8 publications
1
23
0
Order By: Relevance
“…The southwest China sections are probably unique, globally, in that they preserve not only the record of a mass extinction, but also of the smoking gun in the form of the Emeishan large igneous province. Thus, the provinces of Guizhou, Yunnan, and Sichuan preserve the remnants of an extensive Middle Permian carbonate platform composed of the 700-m-thick Maokou Formation (Yang et al, 1999(Yang et al, , 2004Wang and Sugiyama, 2000;Lai et al, 2008;Wignall et al, 2009aWignall et al, , 2009bBond et al, 2010aBond et al, , 2010b. In western Guizhou and Yunnan, volcanics of the Emeishan large igneous province interdigitate with and overlie the Maokou Formation, enabling the fossil record both before and during the eruptions to be examined.…”
Section: Capitanian (Middle Permian) Mass Extinction Extinction Recordmentioning
confidence: 99%
“…The southwest China sections are probably unique, globally, in that they preserve not only the record of a mass extinction, but also of the smoking gun in the form of the Emeishan large igneous province. Thus, the provinces of Guizhou, Yunnan, and Sichuan preserve the remnants of an extensive Middle Permian carbonate platform composed of the 700-m-thick Maokou Formation (Yang et al, 1999(Yang et al, , 2004Wang and Sugiyama, 2000;Lai et al, 2008;Wignall et al, 2009aWignall et al, , 2009bBond et al, 2010aBond et al, , 2010b. In western Guizhou and Yunnan, volcanics of the Emeishan large igneous province interdigitate with and overlie the Maokou Formation, enabling the fossil record both before and during the eruptions to be examined.…”
Section: Capitanian (Middle Permian) Mass Extinction Extinction Recordmentioning
confidence: 99%
“…However, the South China benthic crisis has now been accurately dated to the Jinogondolella altudaensis-Jinogondolella prexuanhanensis conodont zones (Shen and Shi, 2009;Wignall et al, 2009aWignall et al, , 2009bBond et al, 2010aBond et al, , 2010b, making this a mid-Capitanian crisis of short duration, fulfilling the second criterion. Several other marine groups were badly affected in equatorial eastern Tethys Ocean, including corals, bryozoans, and giant alatoconchid bivalves (e.g., Wang and Sugiyama, 2000;Weidlich, 2002;Bond et al, 2010a;Chen et al, 2018). In contrast, pelagic elements of the fauna (ammonoids and conodonts) suffered a later, ecologically distinct, extinction crisis in the earliest Lopingian (Huang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Shortly afterwards it was calculated to be one of the most catastrophic extinction events of the Phanerozoic [3] and since then a considerable body of work has attempted to explore it, focusing on carbonate platforms of southern China and Japan [4][5][6][7][8][9]. Some recent studies have identified extinction horizons preceding the Guadalupian -Lopingian boundary (GLB) by several conodont zones [7,8] and therefore conclude that the mid-Permian marine extinctions constitute an intra-Capitanian event.…”
Section: Introductionmentioning
confidence: 99%